PROYECTO DE FACTIBILIDAD PARA LA CREACIÒN DE UNA EMPRESA DE DISEÑO DE JARDINES EN LA CIUDAD DE LOJA - Enríquez Labanda, Adriana Maribel (2016)
A feasibility project is important because it is the letter of the project in which the most relevant results for potential investors or lenders or shown in summary form. To achieve each of the specific objectives was necessary implementing methods: scientific, inductive, deductive, statistical and mathematical, and respective techniques such as observation, survey, interview and sampling facilitated the development of the different phases of the project investment. The market survey showed that there is an unmet demand 28796 in 2015 and 2020 37527personas unmet demand, which would be our potential customers The study allowed a detailed knowledge of administrative organization, administrative as its mission, vision, objectives: general and specific company "Imperial Gardens" The economic-financial study in order to verify whether the company is profitable, as the net financial indicators (NPV) Current value that was 40.306,73 was applied; The internal rate of return (IRR) of 17.19% the recovery period is 1 year, 4 months and 9 days demonstrating that the project is viable. 5 With the information attained at each stage of the project could establish the feasibility of implementing a landscaping company in the city of Loja. The conclusions and recommendations made in the project stand out as conclusion.- The financial study, allowed to know what was the amount needed to invest, to implement the project which was presented 17371.65 besides knowing that for every dollar invested 0,17ctvs.de would like Recommendation.- profitability and establish the viability which was obtained by the calculations of the financial study is recommended to implement the presented project, since it will receive profitable profits for the company during the 5 years duration of the project will also generate employment.